Gadolinium as a contrast agent for NMR. - Caillé, J M; Lemanceau, B; Bonnemain, B (American Journal of Neuroradiology, 1983)
Gadolinium chloride (GdCl3) was studied as a contrast agent for nuclear magnetic resonance. This rare-earth element dramatically alters proton resonance (paramagnetic moment = 10.8 Bohr magnetons). Acute toxicity was determined by intravenous injections in mice; mean lethal dose was 100-200 mg of GdCl3 . 6 H2O/kg. Changes in T1 of plasma, kidney, liver, and brain of mice and rats were measured after intravenous injections of GdCl3 solution at a concentration of 60 mg gadolinium metal/kg. The apparatus used was a Wh 270 Brucker with a field of 63 kG. The T1 was found to be significantly decreased in plasma, kidney, and liver.